Role of sphingosine kinase in the expression of adhesion molecules on monocytes induced by tumor necrosis factor-alpha : relevance to atherosclerosis - Tuang, Chew Yan. (2008)
In this project, the effect of TNFa on the expression of ICAM-1 and (31 integrin (receptor of endothelial VCAM-1) on monocytes (U937 cells) was studied. In addition, an attempt was made to investigate the involvement of SPHK in this TNFa signaling pathway and to identify the mediators involved in the cascade. It was found that TNFa up-regulated the expression of ICAM-1 and integrin pi on monocytes and SPHK was involved in the signaling cascade.